Behavioral Relations in Across-Culture Distribution Systems: Influence, Control and Conflict in U.S. Japanese Marketing Channels - Johnson, Jean L.; Sakano, Tomoaki; Onzo, Naoto (Journal of International Business Studies, 1990)
A mail survey of Japanese distributors of U.S. products provided data for an examination of how perceptions of influence affect control and conflict in the relationship. Results indicated that aggressive influence evoked resistance and conflict, while more subtle influence strategies appeared to reduce conflict. Results suggested that influence, as practiced in western channels, may not be effective in relationship such as these.